2013
DOI: 10.1111/nep.12031
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for chronic kidney disease among HIV‐infected antiretroviral therapy‐naïve patients in Mainland China: A multicenter cross‐sectional study

Abstract: The incidence of CKD is high in Chinese HIV-infected ART-naïve patients. Traditional risk factors for renal disease, such as advancing age, HCV co-infection, and higher plasma viral load were correlated with CKD in the present patient samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 26 publications
(44 reference statements)
3
23
2
Order By: Relevance
“…A summary table with the results of study selection including the list of enrolled and excluded papers are reported in Additional file 2, 3, and 4. We identified 19 studies (146,151 unique patients with HIV) [Szczech et al, ; Tedaldi et al, ; Szczech et al, ; Ando et al, ; Di Biagio et al, 2011; Flandre et al, ; George et al, ; Yanagisawa et al, ; Peters et al, ; Jotwani et al, ; Kalayjian et al, ; Mocroft et al, ; Bickel et al, ; Cao et al, ; Estrella et al, ; Lucas et al, ; Reynes et al, ; Banerjee et al, ; Hsieh et al, ]. Among longitudinal studies (n = 10), eight evaluated the incidence of CKD, and two the incidence of proteinuria.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A summary table with the results of study selection including the list of enrolled and excluded papers are reported in Additional file 2, 3, and 4. We identified 19 studies (146,151 unique patients with HIV) [Szczech et al, ; Tedaldi et al, ; Szczech et al, ; Ando et al, ; Di Biagio et al, 2011; Flandre et al, ; George et al, ; Yanagisawa et al, ; Peters et al, ; Jotwani et al, ; Kalayjian et al, ; Mocroft et al, ; Bickel et al, ; Cao et al, ; Estrella et al, ; Lucas et al, ; Reynes et al, ; Banerjee et al, ; Hsieh et al, ]. Among longitudinal studies (n = 10), eight evaluated the incidence of CKD, and two the incidence of proteinuria.…”
Section: Resultsmentioning
confidence: 99%
“…Five cohort studies (n = 13,853 unique patients), four having cross‐sectional design addressed the prevalence of CKD in adults with HIV‐HCV co‐infection [Di Biagio et al, 2011; Mocroft et al, ; Bickel et al, ; Cao et al, ; Hsieh et al, ] (Table ). The relationship between HCV‐HIV co‐infection and increased frequency of lowered GFR did not reach statistical significance, adjusted OR, 1.58 (95%CI, 0.81; 2.34, NS).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, beyond ART, comprehensive multi-system screening and management has been recognized as an increasingly important component of HIV care. On the one hand, HIV infection and its associated immune activation has been identified as an independent risk factor for many non-AIDS complications, including atherosclerosis, cardiovascular diseases, osteoporosis, and renal diseases [19][20][21][22][23][24]. On the other hand, lifelong use of ART also exerts systemic influences including but not limited to alterations in lipid and glucose metabolism, liver and renal functions, bone and mineral homeostasis, and neuropsychiatric changes.…”
Section: Promoting Multidisciplinary Care and Integrating The Hiv/aidmentioning
confidence: 99%
“…This trend is limited to the African population. In China, in the work of Cao et al [15], we note a male predominance with a sex ratio of 2.87. This difference in sex can be explained either by the fact that women consult late because of their cultural weight, or because they are more affected by HIV or by the influence of female hormones such as estrogen.…”
Section: Discussionmentioning
confidence: 66%